2022
DOI: 10.1101/2022.03.17.484053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maintaining hypoxia environment of subchondral bone alleviates osteoarthritis progression

Abstract: Abnormal subchondral bone remodeling featured by over-activated osteoclastogenesis leads to articular cartilage degeneration and osteoarthritis (OA) progression, but the mechanism is still unclear. In this study, we used lymphocyte cytosolic protein 1 (Lcp1) knock-out mice to suppress subchondral osteoclast formation in mice OA model with anterior cruciate ligament transection (ACLT) and Lcp1-/- mice showed decreased bone remodeling and sensory innervation in subchondral bone accompanied by retarded cartilage … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Osteoarthritis (OA) is a widespread irreversible articular disease marked by articular cartilage deterioration and subsequent osteophytes. 1,2 It affects millions of people worldwide, especially older people over 60 years old. 3 The current mainstream OA treatment options fall into three categories: physical therapy, pharmacotherapy and surgery.…”
mentioning
confidence: 99%
“…Osteoarthritis (OA) is a widespread irreversible articular disease marked by articular cartilage deterioration and subsequent osteophytes. 1,2 It affects millions of people worldwide, especially older people over 60 years old. 3 The current mainstream OA treatment options fall into three categories: physical therapy, pharmacotherapy and surgery.…”
mentioning
confidence: 99%
“…The results of KEGG analysis showed that RJNTF could treat KOA by interfering with multiple signaling pathways such as NF-κB, apoptosis, HIF-1 signaling pathway, JAT-STAT signaling pathway and IL-17 signaling pathway (Fig. 2B) (31)(32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time the ML model results are con rmed by classical statistics, correlation analysis, whereas the literature data are contradictory. Different studies consider high or low pancreatic duct diameter as risk factors; the observations on BMI and surgical technics are controversial in general [10,15,39]. Being important for ML models development, BMI was not correlated with pancreatic stulas development.…”
Section: Discussionmentioning
confidence: 98%